KAJIAN SYSTEMATIC LITERATURE REVIEW (SLR): PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) DALAM MENINGKATKAN LITERASI MEMBACA SISWA SEKOLAH DASAR - Nabila Kurnia Asdi; Sri Sumartiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Reading literacy is a basic competency that plays a crucial role in the academic success of elementary school students because it serves as the foundation for interdisciplinary learning skills. However, various studies indicate that basic reading literacy skills in Indonesia remain low due to learning approaches that have not been adapted to students' ability levels. This study aims to analyze the effectiveness of the Teaching at the Right Level (TaRL) approach in improving elementary school students' reading literacy through the Systematic Literature Review (SLR) method. The review was conducted on ten SINTA-indexed scientific articles published between 2020 and 2025, focusing on the implementation of TaRL in elementary schools. The synthesis results indicate that the TaRL approach is effective in improving reading comprehension, reading speed, and reading fluency in students at various ability levels. TaRL has also been shown to strengthen student self-confidence, encourage active participation, and improve the effectiveness of literacy learning through formative assessment and grouping based on actual ability levels. Factors supporting the successful implementation of TaRL include teacher readiness, support for contextual learning media, intensive training, and involvement of school literacy communities. However, implementation challenges remain, including time constraints, teacher-student ratios, and curriculum policy adaptations. This study confirms that the TaRL approach has the potential to be an inclusive and contextual learning strategy for strengthening a culture of reading literacy in Indonesian elementary schools.